PENINGKATAN KETERAMPILAN MENULIS CERPEN MENGGUNAKAN APLIKASI XMIND PADA SISWA KELAS XI SMAN 15 ADIDARMA - Delfa Suryasi; Intan Kemala Sari; Wahidah Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Short story writing skills are one of the important competencies in Indonesian language learning at the senior high school (SMA) level. However, in reality, many students still experience difficulties in developing ideas, structuring plots, and organizing the elements of a short story in a logical and coherent manner. One of the contributing factors is the limited availability of learning media that can assist students during the pre-writing stage. This study aims to determine the effect of using the XMind application on improving the short story writing skills of eleventh-grade students at SMAN 15 Adidarma. The study employed a quantitative approach with a one-group pretest–posttest design. The research sample consisted of eleventh-grade students selected through purposive sampling. Data were collected through short story writing tests administered before and after the implementation of the XMind application, with assessment based on short story writing skill indicators, including theme, plot, characterization, setting, language style, and moral message. Data analysis techniques included normality testing and the paired samples t-test. The results showed that the use of the application did not have a significant effect on students’ short story writing skills. The paired samples t-test results indicated a significance value greater than 0.05, meaning that the null hypothesis stating that there is no significant effect was accepted. Therefore, the use of the XMind application has not demonstrated a significant improvement in the short story writing skills of eleventh-grade students at SMAN 15 Adidarma. Thus, the use of the XMind application in short story writing instruction needs to be adjusted to students’ characteristics and combined with appropriate stages and strategies in writing instruction in order to better support the process of idea development and short story organization